The zebrafish genome in context: ohnologs gone missing - Postlethwait, John H. (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2007)
Some zebrafish genes appear to lack an ortholog in the human genome and researchers often call them “novel” genes. The origin of many so‐called “novel” genes becomes apparent when considered in the context of genome duplication events that occurred during evolution of the phylum Chordata, including two rounds at about the origin of the subphylum Vertebrata (R1 and R2) and one round before the teleost radiation (R3). Ohnologs are paralogs stemming from such genome duplication events, and some zebrafish genes said to be “novel” are more appropriately interpreted as “ohnologs gone missing”, cases in which ohnologs are preserved differentially in different evolutionary lineages. Here we consider ohnologs present in the zebrafish genome but absent from the human genome. Reasonable hypotheses are that lineage‐specific loss of ohnologs can play a role in establishing lineage divergence and in the origin of developmental innovations. How does the evolution of ohnologs differ from the evolution of gene duplicates arising from other mechanisms, such as tandem duplication or retrotransposition? To what extent do different major vertebrate lineages or different teleost lineages differ in ohnolog content? What roles do differences in ohnolog content play in the origin of developmental mechanisms that differ among lineages? This review explores these questions. J. Exp. Zool. (Mol. Dev. Evol.) 308B:563–577, 2007. © 2006 Wiley‐Liss, Inc.